Bali Sruti Strategy in Addressing Gender Inequality in Bali - Larasati, Ria Agustina (International Journal of Management and Business, 2025)
This article examines the strategies implemented by Bali Sruti as a civil society organization focused on women's empowerment and gender equality in Bali. This study employs a descriptive qualitative approach to explore Bali Sruti’s strategies for addressing gender inequality in Bali. Data collection techniques are carried out through literature studies, interviews, and participatory observations of activities organized by Bali Sruti, such as training, public campaigns, and policy advocacy. This study uses a qualitative method to explore how Bali Sruti uses local cultural values to fight gender inequality through advocacy, education, community support, and partnerships at national and international levels. The results showed that the Bali Sruti strategies have a positive contribution to increasing the awareness and participation of Balinese women. The efforts were carried out through legal campaigns and the establishment of female schools where vulnerable women, such as female heads of family, women with disabilities, women with low income, and victims of sexual violence, were given a forum to share and provide an understanding that they have the right to speak. The results of this study provide valuable insights for civil society organizations and policymakers, encouraging the adoption of community-based strategies to promote gender equality within culturally traditional communities.